Languages for Embedded Systems and their Applications Selected Contributions on Specification, Design, and Verification from FDL'08 - Radetzki, Martin (Lecture Notes in Electrical Engineering, 2009)
Embedded systems take over complex control and data processing tasks in diverse application fields such as automotive, avionics, consumer products, and telecommunications. They are the primary driver for improving overall system safety, efficiency, and comfort. The demand for further improvement in these aspects can only be satisfied by designing embedded systems of increasing complexity, which in turn necessitates the development of new system design methodologies based on specification, design, and verification languages. The objective of Languages for Embedded Systems and their Applications is to provide researchers and designers with an overview of current research trends, results, and application experiences in computer languages for embedded systems. The book builds upon the most relevant contributions to FDL'08, the premier international conference specializing in this field. These contributions have been selected based on the results of reviews provided by leading experts from research and industry. In many cases, the authors have improved their original work by adding breadth, depth, or explanation.